A Research on the Optimization of Certain Plasma Spraying Parameters to Enhance the Shear Adhesion Strength of WC-Ni Coatings on FC300 Material Surfaces - Thao, Dang Xuan; Tuan, Chu Anh; Cuong, Pham Duc (Engineering, Technology & Applied Science Research, 2025)
Metal-ceramic coatings applied via plasma spraying offer a promising solution for improving the operational durability of machine components. However, the quality of the coating on the surfaces of these components depends on various factors. Among these, the adhesion of the coating plays a crucial role in the lifespan of the component when subjected to relative sliding friction. In addition to material properties, the spraying process parameters have a substantial impact on the coating's adhesion to the substrate metal. This research presents the results of optimizing three spraying parameters: spray current intensity (Is), powder feed rate (ms), and spray distance (Ls), concerning the sliding shear adhesion strength ( ) of the metal-ceramic coating with a composition of 34% WC and 45% Ni (WC-45Ni) deposited on the surface of gray cast iron FC300. The coatings were applied using the Atmospheric Plasma Spraying (APS) technique, with particles impacting the substrate surface perpendicularly at a 90° angle. The shear adhesion strength of the coating was determined using a universal compression testing machine (BESTUTM 500HH, Korea). The results indicated that all three input parameters significantly affect the output parameter, with spraying current intensity being the most influential, followed by spraying distance, and powder feed rate recorded as the least influential factor. The optimized spraying parameters, determined through Analysis of Variance (ANOVA), were Is = 682.3 A, ms = 31.5 g/min, and Ls = 170.2 mm, resulting in a practical sliding shear adhesion strength of = 51.64 MPa. Furthermore, the experimental results were validated with an error of approximately 0.9% compared to the predicted optimal value.